Electrical brain stimulation in different variants of primary progressive aphasia: A randomized clinical trial. Issue 1 (4th September 2018) - Tsapkini, Kyrana; Webster, Kimberly T.; Ficek, Bronte N.; Desmond, John E.; Onyike, Chiadi U.; Rapp, Brenda; Frangakis, Constantine E.; Hillis, Argye E.
Abstract: Introduction: Transcranial direct current stimulation (tDCS) has been recently shown to improve language outcomes in primary progressive aphasia (PPA) but most studies are small and the influence of PPA variant is unknown. Methods: Thirty‐six patients with PPA participated in a randomized, sham‐controlled, double‐blind, within‐subject crossover design for 15 daily sessions of stimulation coupled with written naming/spelling therapy. Outcome measures were letter accuracy of treated and untreated words immediately after and at 2 weeks and 2 months posttreatment. Results: tDCS treatment was more effective than sham: gains for treated words were maintained 2 months posttreatment; gains from tDCS also generalized to untreated words and were sustained 2 months posttreatment. Different effects were obtained for each PPA variant, with no tDCS advantage for semantic variant PPA. Discussion: The study supports using tDCS as an adjunct to written language interventions in individuals with logopenic or nonfluent/agrammatic PPA seeking compensatory treatments in clinical settings. Highlights: Anodal tDCS over the left IFG enhances effects of written naming therapy in PPA. tDCS helps written naming benefits generalize in logopenic and nonfluent PPA. No generalization occurs for semantic variant PPA with left IFG tDCS. Behavioral gains sustain for 2 months after tDCS but rescind after sham. tDCS is a potentially useful adjunct to language therapy in PPA.